Load Induced Error Identification and Camber Curve Design of a Large-Span Crossbeam. (11th December 2013) - Cheng, Qiang; Luo, Rui; Gu, Peihua; Wang, Zhiliang; Guo, Hongsheng
Abstract : Load induced errors aroused by internal masses of machine tool components and external cutting forces are a main contributor that influences machining accuracy. A mathematical model for load induced errors identification of large-span crossbeam in heavy-duty machine tool was proposed. According to the identified load induced errors, a method for optimisation of the guideway camber curve on crossbeam by particle swarm optimisation was proposed. Geometric errors of y -axis along cambered crossbeam and noncambered crossbeam were calibrated, and multibody system theory was also introduced to predict theoretically the machining accuracy of machine tool with two kinds of crossbeam. The comparisons between two kinds of crossbeam show that after cambering, the geometric errors are decreased and can meet the requirements of ISO standard, and the machining accuracy is enhanced remarkably too. In addition, the indirect dynamic straightness error of z -direction along cambered crossbeam was measured by displacement sensors, and the response results show that even though at the start-stop moment, the straightness error is also within the reasonable range of ISO standard.